(untitled) (Al-Academy, 2016)
Was and military music still in Iraq whatever tributary of Music, where contributed Brphi Iraqi music musicians, authors and composers of musicians skilled and qualified teachers, was, and still have a big role in the growth and prosperity and progress of contemporary Iraqi music through active and vital role and make a lot of musical tenders excellence in various military and civilian walks of life whether it be in the days of war or peace.As it is the military music schools and the main source of the most important in the education of these machines and training. Therefore occupies the military musicians in Iraq prestigious and important, particularly in the Iraqi National Symphony Orchestra started the forefront of the musical instruments aerobic and rhythmic position.